Transcriptome analysis of sugar and acid metabolism in young tomato fruits under high temperature and nitrogen fertilizer influence - Zheng, Yanjiao; Yang, Zaiqiang; Luo, Jing; Zhang, Yao; Jiang, Nan; Khattak, Wajid Ali (Frontiers in Plant Science, 2023)
Environmental temperature and nitrogen (N) fertilizer are two important factors affecting the sugar and organic acid content of tomato fruit. N is an essential nutrient element for plant growth and development, and plays a key role in regulating plant growth, fruit quality and stress response. However, the comparative effect of different N fertilizer levels on the accumulation of soluble sugar and organic acid in tomato young fruit under high temperature stress and its mechanism are still unknown. In this paper, three N fertilizer levels (N1, N2, N3) combined with two temperatures (28/18℃, CK; 35/25℃, HT) were used to study the effects of N fertilizer, HT and their interaction on the soluble sugar and organic acid components, content, metabolic enzyme activity and the expression level of key genes in tomato young fruit, revealing how N fertilizer affects the sugar and acid metabolism of tomato young fruit under HT at physiological and molecular levels. The results showed that the content of soluble sugar and organic acid in tomato young fruit under HT exposure was increased by appropriate N fertilizer (N1) treatment, which was due to the accumulation of glucose, fructose, citric acid and malic acid. High N (N3) and HT exposure had a negative impact on soluble sugar and reduce sugar accumulation. Further studies showed that due to the up-regulation of the expression of sucrose metabolizing enzyme genes (CWINV2, HK2, SPS, PK) and sucrose transporter (SUT1, SUT4, SWEETs) in tomato, N fertilizer increased the accumulation of soluble sugar by improving the sucrose metabolism, absorption intensity and sucrose transport of fruit under HT exposure. Due to the increase of PEPC gene expression, N fertilizer increased the accumulation of citric acid and malic acid by improving the TCA cycle of fruit under HT exposure. The results can provide theoretical support for the correct application of N fertilizer to improve the quality of tomato fruit under HT exposure.